Intraday and inter-day reliability of sprinting kinetics in young female athletes measured using a radar gun - Talukdar, K.; Harrison, C.; McGuigan, M. (Measurement in Physical Education and Exercise Science, 2021)
The radar gun is a valid and practically feasible tool to measure sprinting speed and kinetics among athletes. However, its reliability in youth populations, particularly females, is unknown. Therefore, this study aimed to evaluate the intraday and inter-day reliability of sprinting kinetics using a radar gun to measure force (Fo), theoretical velocity (Vo), maximal velocity (Vmax), power max (Pmax) and split times (0-30 m) in young female athletes. Twenty-nine young female athletes aged 13.7 ± 0.89years (height 1.62 ± 0.06 m; weight 51.7 ± 8.41 kg) from sports teams at a private girl`s college participated. The assessment included four sprints over 30 m (separated by 7days) for inter-day analysis and two sprints over 30 m on the same day for intraday analysis. Moderate to strong intraclass correlation coefficient 0.74 to 0.98 with a coefficient of variation ranging from 1.70% to 12.70% across all kinetic variables were reported for both intraday and inter-day reliability. The smallest worthwhile change ranged from 1.17% to 6.89%. All tests were identified as having acceptable reliability.